Exploring lipodystrophy gene expression in adipocytes: unveiling insights into the pathogenesis of insulin resistance, type 2 diabetes, and clustering diseases (metabolic syndrome) in Asian Indians - Saxena, Aditya; Tiwari, Pradeep; Gupta, Shalu; Mandia, Rajendra; Banshiwal, Ramesh C.; Lamoria, Ravinder Kumar; Anjana, Ranjit Mohan; Radha, Venkatesan; Mohan, Viswanathan; Mathur, Sandeep Kumar (Frontiers in Endocrinology, 2024)
Background: Studying the molecular mechanisms of lipodystrophy can provide valuable insights into the pathophysiology of insulin resistance (IR), T2D, and other clustering diseases (Metabolic syndrome, MetS) and its underlying adipocentric disease (MetS disease).Methods: A high-confidence lipodystrophy gene panel comprising fifty genes was created and their expressions were measured in visceral and subcutaneous (both peripheral and abdominal) adipose depot of MetS and non-MetS individuals at a tertiary care medical facility.Results: Most lipodystrophy genes showed significant downregulation in MetS individuals compared to non-MetS in both subcutaneous and visceral depots. In the abdominal compartment all the genes showed relatively higher expression in visceral depot as compared to their subcutaneous counterpart and this difference narrowed with increasing severity of MetS. Their expression level shows an inverse correlation with T2D, MetS, and HOMA-IR and with other T2D-related intermediate traits. Results also demonstrated that individualization of MetS patients could be done based on adipose tissue expression of just twelve genes.Adipose tissue expression of lipodystrophy genes show an association with MetS and its intermediate phenotypic traits. Mutations of these genes are known to cause congenital lipodystrophy syndromes, whereas, their altered expression in adipose tissue contributes to pathogenesis of IR, T2D and MetS .